Тайна булавки: [перевод с английского] / Эдгар Уоллес - Уоллес Эдгар (Его Величество Детектив, 2009)
Экземпляры: ф.5 (20221025) / Инвентарный номер: 62655 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: У 63 / ГРНТИ: 17.82.30 / ББК: 84(4Вел)-4